Strategies for Increasing Acceptance of English as a Foreign Language in Higher Education Environments - Sri Rahayu; Tenri Ampareng (Journey: Journal of English Language and Pedagogy, 2025)
This study examines strategies to increase English language acceptance in Indonesian universities, considering the importance of English proficiency in the global academic context. Through a qualitative approach with a literature study method, this study analyzes various literature and previous research results to identify challenges and solutions in increasing English acceptance. The results show that the English language acceptance rate among students is still not optimal, with the main obstacles being high language anxiety and low intrinsic motivation. Factors that affect English language acceptance include psychological aspects such as self-efficacy and anxiety, as well as external factors such as the quality of the learning environment and institutional support. This research proposes a comprehensive development strategy that integrates modern pedagogical approaches, such as project-based learning and Content and Language Integrated Learning (CLIL), with the support of learning technology. Mentoring programs and peer support groups have proven to be effective in creating a supportive learning environment. The evaluation of the implementation of the strategy showed a gradual increase in English language acceptance, characterized by a decrease in the level of language anxiety and an increase in student participation in learning activities. These findings make a significant contribution to the development of English learning programs in higher education that are more effective and sustainable.